Analisis Kesesuaian Metode Pembelajaran dengan Rencana Pelaksanaan Pembelajaran (RPP) dari Capaian Pembelajaran Pendidikan Agama Islam di Madrasah Tsanawiyah Al-Itqon Cibungbulang Bogor - Rini Irma Yunita Apri Purwanti; Primarni, Ami; Srihartini, Yusi (Jurnal Dirosah Islamiyah, 2024)
"Analysis of the Suitability of Learning Methods with the Learning Implementation Plan (RPP) for Islamic Religious Education at Madrasah Tsanawiyah Al-Itqon Cibungbulang Bogor" The background of this research is the Learning Implementation Plan whose contents are not in accordance with the implementation of learning in the field. 1) What is the learning method for Islamic religious education at MTs Al-Itqon Cibungbulang Bogor? 2. What is the Learning Implementation Plan at MTs Al-itqon Cibungbulang Bogor? 3. What are the learning methods used in the learning implementation plan (RPP) for Islamic religious education at Al-itqon Madrasah Tsanawiyah Bogor?  The aim of this research is to find out: 1. Islamic religious education learning methods at MadrasahnTsanawiyah Al-Itqon Cibungbulang Bogor. 2. Learning Implementation Plan (RPP) material for Islamic religious education at Madrasah Tsanawiyah Al-Itqon Cibungbulang Bogor. 3. What are the learning methods used in the plan for implementing Islamic religious education at Madrasah Tsanawiyah Al-Itqon Bogor?  This research method uses qualitative field methods. Data was collected using several qualitative data collection techniques, namely; 1). interview, 2). observation, 3). documentation, and 4). focused discussion (Focus Group Discussion). The research described previously can be concluded. 1. The Islamic religious education learning method at Madrasah Tsanawiyah Al-Itqon Bogor is: a. Lecture Method b. Question and Answer Method c. Discussion Method d. Demonstration Method e. Experimental Method f. Inquiry Method g. Unit Teaching Method h. Simulation Method i. Assignment Method j. Group Work Method. The learning implementation plan (RPP) for Islamic religious education at Madrasah Tsanawiyah Al-Itqon Bogor contains learning objectives, learning materials and learning methods and steps for learning activities. The learning method used in the Learning Implementation Plan (RPP) for Islamic religious education at Madrasah Tsanawiyah Al-Itqon Bogor is by using a learning by doing system, inquiry method, question and answer method, demonstration method, and lecture method.